An analysis of the Cordylus cordylus complex (Reptilia: Cordylidae) in the Southwestern Cape; - Mouton, Pieter leFras Nortier (Stellenbosch : Stellenbosch University, 2012)
Thesis(Ph.D.)-University of Stellenbosch,1985.